￼Embodied mental rotation: A special link between egocentric ￼transformation and the bodi - Kaltner, Sandra; Riecke, Bernhard E.; Jansen, Petra (North American Society for Sport Psychology and Physical Activity (NASPSPA), 2015)
In mental rotation there are two different classes of mental transformation strategies, which seem to represent different cognitive operations: object-based and egocentric transformations (Zacks, Mires, Tversky, & Hazeltine, 2002). Whereas in object-based transformations the observer’s position remains fixed, in egocentric transformation tasks participants are asked to mentally change their own perspective (Devlin & Wilson, 2010). This study was conducted to investigate the involvement of motor processes in both transformation types against the background of the embodiment-approach. The key idea of this renewed viewpoint is that many cognitive processes that were formerly defined as purely “cognitive”, are also deeply rooted in body-related experiences with the environment. Based on the previous literature, egocentric rotations are supposed to be embodied to a higher extent (Kessler & Thomson, 2010). The investigation of this issue contained the recruitment of motor experts vs. non-motor experts to alternate the degree of motor expertise. Furthermore, by analyzing stimuli using the own versus another person’s body, we wanted to examine if the embodiment is more distinct in egocentric transformations than in object-based rotations.
Keywords: Riecke; Riecke_2015; bernhard-riecke; petra-jansen; poster; posterWithoutPaper; sandra-kaltner; talkWithoutPaper